2019
DOI: 10.1002/est2.44
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of using graded porosity on the thermal performance of the encapsulated ice thermal energy storage tank

Abstract: The storage tank has great impact on the performance of ice thermal energy storage (ITES) system. Previous researches show that enhanced temperature gradient in the tank improves the thermal performance of system. This study deals with the investigation for determining the effect of using graded porosity in the storage tank of encapsulated ITES system. In this study, it was researched that the effects of uniform, two‐graded, and three‐graded porosities inside the storage tank. Energy equation in porous medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Although thermodynamic analyses of sensible and latent TES systems are different from each other, the approach for both systems is quite similar. While one of our aim here is to investigate viscous heating effect on the energy and exergy efficiencies as studied by MacPhee and Dincer for a latent TES system, second purpose is to investigate the effect of the heat leakage on the thermodynamic efficiencies as investigated in References 33, 50, and 51.…”
Section: Resultsmentioning
confidence: 99%
“…Although thermodynamic analyses of sensible and latent TES systems are different from each other, the approach for both systems is quite similar. While one of our aim here is to investigate viscous heating effect on the energy and exergy efficiencies as studied by MacPhee and Dincer for a latent TES system, second purpose is to investigate the effect of the heat leakage on the thermodynamic efficiencies as investigated in References 33, 50, and 51.…”
Section: Resultsmentioning
confidence: 99%
“…The system performance and the tank thermal stratification showed improvement in all cases. Erdemir and Altuntop presented an analytical model of encapsulated ice thermal energy storage (ITES) system to determine the effect of porosity structure of the tank on the thermal performance of the tank. It was found that the lower porosity supplied higher thermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…Of the installed cold thermal storage systems, 80-85% of these systems use ice storage, with the bulk of the remainder using chilled water and a small percentage using eutectic salts [64]. These ice storage systems can be broken down into four major types: ice harvesting, ice-on-coil (which can be further categorized as internal and external melt), ice slurry and encapsulated ice systems [64,65]. Each of these systems have their own advantages and disadvantages, however ice-on-coil systems have shown promising results in smaller systems including in a study by Lee and Jones [66] which used an ice-on-coil storage tank with a 150 kWh storage capacity and direct refrigerant coils, and connected to a simulated 10,000 ft 2 building.…”
Section: Ice Storagementioning
confidence: 99%